OPTIMALISASI PELAYANAN PUBLIK DALAM PELAKSANAAN e-KTP GUNA MEMPERKOKOH KETAHANAN WILAYAH (Studi Di Kelurahan Kalibaru Kecamatan Cilodong Kota Depok, Jawa Barat) - Muhtarhadi Nursalim (Jurnal Ketahanan Nasional, 2014)
This paper explained public service optimization in e-KTP implementation to strengthened regional resilience. The problem showed due the e-KTP implementation less than 100% achievement at the end of 2012. The purpose of this paper was discovering the public service quality condition of the e-KTP implementation in Kalibaru sub-district Cilodong District Depok, identify the obstacle of the e-KTP implementation in Kalibaru sub-district Cilodong District Depok, and establish the public service optimization strategy of the e-KTP implementation in Kalibaru sub-district Cilodong District Depok, and also the implication on regional resilience. The method of this paper was interview and fi eld observation. The location election method is conducted with purposive sampling. The variable of this research was public service optimization of the e-KTP implementation at the Kalibaru sub-district, namely the Organization Structure of the e-KTP Service, Service Administration of the e-KTP Service, human resource of the e-KTP Service, facilities and infrastructure of the e-KTP. The result of this paper showed the strategies to optimized the e-KTP service implementation at Kalibaru sub-District were (a) increase the coordination, (b) Implementing MSDN functions namely management function and operational. Therefore the e-KTP implementation would be able to supported Regional resilience.Keywords: Public Service, e-KTP, Regional Resilience